LEGAL STANDING KOMISI PEMBERANTASAN TINDAK PIDANA KORUPSI (KPK) DALAM SENGKETA KEWENANGAN LEMBAGA NEGARA DI MAHKAMAH KONSTITUSI - Eviani Yuliantari, I Gusti Ayu (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2015)
This paper takes the title: "Legal Standing of the Komisi Pemberantasan Korupsi (KPK) in Case Dispute Authority of State Institutions in the Mahkamah Konstitusi". The research in this paper addresses two problems that are associated with the KPK as a state institution in the UUD NRI 1945 and the legal standing of the KPK, which can be a Party to the Dispute Authority of State Institutions in the Mahkamah Konstitusi by the UUD NRI 1945. The method used in this research is normative legal research, because this research seeks to discuss or review the legal norm in this case the norms of legislation to determine the synchronization either vertically or horizontally. This thesis explains that the KPK is a state agency whose authority is not clearly regulated by the UUD NRI 1945. Therefore, the KPK does not have legal standing as an applicant or respondent in a lawsuit filed in the Mahkamah Konstitusi relating to dispute the authority of state institutions because the authority is the Commission does not expressly provided in UUD NRI Tahun 1945 but by law.
Keywords: Legal Standing; State Institutions; State Agency Dispute Authority